2017
DOI: 10.5607/en.2017.26.2.104
|View full text |Cite
|
Sign up to set email alerts
|

A High-fat Diet Induces a Loss of Midbrain Dopaminergic Neuronal Function That Underlies Motor Abnormalities

Abstract: Movement defects in obesity are associated with peripheral muscle defects, arthritis, and dysfunction of motor control by the brain. Although movement functionality is negatively correlated with obesity, the brain regions and downstream signaling pathways associated with movement defects in obesity are unclear. A dopaminergic neuronal pathway from the substantia nigra (SN) to the striatum is responsible for regulating grip strength and motor initiation through tyrosine hydroxylase (TH) activity-dependent dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…Alternatively, DA synthesis could be affected by an obesogenic diet. In mice, fed on a high fat diet, the expression of midbrain tyrosine hydroxylase (TH) was reduced [81], however increased in the hypothalamus [76]. TH is the rate limiting enzyme in DA synthesis, and a reduced activity could undelay the reduced DA concentrations as observed in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Alternatively, DA synthesis could be affected by an obesogenic diet. In mice, fed on a high fat diet, the expression of midbrain tyrosine hydroxylase (TH) was reduced [81], however increased in the hypothalamus [76]. TH is the rate limiting enzyme in DA synthesis, and a reduced activity could undelay the reduced DA concentrations as observed in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Regarding the motor aspects, several studies revealed that HFDs decreased motor function and movement in the OFT. Mice fed an HFD for 20 weeks exhibited decreased movement in the OFT and an increase in the number of missteps in a vertical grid test when compared to mice fed a normal diet [24]. Another study showed that, as compared to lean mice, DIO mice with their activity levels measured using the OFT every two weeks had fewer and slower movements beginning at week 4 and persisting through week 18 [25].…”
Section: Discussionmentioning
confidence: 99%
“…As DA neurons possess a large amount of GAP-43, and decreased GAP-43 in nigrostriatal DA neurons was observed in an animal model of the presymptomatic period of PD [34], this supports our finding of HFD-induced reduction of dendritic spine density in the SN and striatum. Other proposed mechanisms linking HFD to alterations in the DA system include oxidative stress [35], mitochondrial dysfunction [36], and decreased phosphorylation of c-Jun N-terminal kinase [24] and Akt [37]. SN was found to be more vulnerable to changes in energy state such as glucose signaling as compared to the striatum and cerebral cortex while using db/db and HFD models [26].…”
Section: Discussionmentioning
confidence: 99%
“…After being given a HFD for 20 weeks, mice displayed reduced locomotion in the open field test and increased missteps in a vertical grid test. These changes were associated with TH depletion in the SN and striatum ( Jang et al, 2017 ). Kao et al (2019) recently demonstrated that mice fed a HFD (60% fat) for 20 weeks presented decreased locomotor function, loss of dopaminergic neurons in the SN, and dendritic spine density reduction.…”
Section: Metabolic Diseases As a Risk Factor For Neurodegenerative DImentioning
confidence: 99%